Dynamic modelling of a single link flexible manipulator in vertical motion using swarm and genetic optimisation - Md. Zain, B. A.; Tokhi, M. Osman; Toha, Siti Fauziah (2009)
In this research, particle swann optimisation (PSO) and genetic algorithm (GA) are used to model a single-link flexible manipulator. Investigations focus on characterizing the system from input torque to hub-angle, hub-velocity and end-point acceleration. A simulation environment characterizing the system behaviour in vertical motion is used as a platfonn to test and verifY the PSO and GA based transfer function models. The environment is based on finite difference discretisation of the goveming dynamic equation of motion of the system. The system is treated as a single-input multioutput system, and the input/output data collected is used with PSO and GA to develop models of the system based on autoregressive moving average model structure and one-step-ahead prediction. Comparative assessment of the results is presented and discussed in the time and frequency domains.